OPTIMIZATION OF YOGURT FERMENTED MILK PRODUCTS WITH THE ADDITION OF NATURAL STABILIZER BASED ON LOCAL POTENTIAL OF TARO STARCH (COLOCASIA ESCULENTA) - Aju Tjatur Nugroho Krisnaningsih; Dyah Lestari Yulianti; Imam Thohari; Puguh Surjowardojo (UPT Penerbitan Universitas Jember, 2016)
The aims of research were to improve the quality of the final product through the use of yogurt stabilizer based on local potential, easily obtainable stock and has a low price, namely taro starch (Colocasia esculenta). The method of research was laboratory experiment arranged in completely randomized design factorial. The first factor is the level of taro starch with 4 treatments (0%, 1%, 2%, 3%). The second factor is the concentration of starter with 3 treatments (1%, 3%, 5%). Each treatment was repeated 3 times. The variables measured and analyzed: 1) pH, 2) the acidity, 3) viscosity. The data were analyzed by Anova. If significant the Duncan’s Multiple Range Test was applied.The results showed the addition of stabilizer level provides a significant influence on the pH, acidity and viscosity of yogurt (P <0.01) but concentration starter not significant of pH and viscosity (P> 0.05) but very real effect on the acidity of the yogurt (P <0.01). Interaction taro starch level and inoculation starter does not give effect to the quality of the yogurt based on physico-chemical properties. pH yogurt with the addition of stabilizer level of 1%, 2% and 3% produce ideal pH after fermentation for ready consumption of 3.9. The acidity of the yogurt without stabilizer (0%) was 1,52% -2.02%. Addition of stabilizers 1% and above decreased the acidity of the yogurt. Level 3% of stabilizer provides the highest viscosity value of 27620 cP yogurt. While the lowest viscosity of the yogurt without addition of stabilizer (0%) of 840 Cp. Conclusions of research that the stabilizer taro starch level of 1% contribute to produce optimal quality yogurt products.